Beyond the City Limits: Literary Reception of "Nicosia" and Perspectives of 4th Semester Arabic Language and Literature Students - Rofiqi, Rofiqi; Ma’rifatul Munjiah (Jurnal Onoma: Pendidikan, Bahasa, dan Sastra, 2025)
This study examines the literary reception of Saadi Youssef's short story "Nicosia" among 14 fourth-semester undergraduate students of Arabic Language and Literature from the 2023 cohort at the Faculty of Humanities, Universitas Islam Negeri Maulana Malik Ibrahim Malang, who are categorized as general readers. The literary reception approach highlights how literary works are received, experienced, and processed by readers, focusing on the interaction between text and reader in creating meaning. The short story was chosen due to its thematic relevance to the main character, Tahir's, journey in understanding identity and social reality amidst conflict, and its Arabic language level, which aligns with the respondents' proficiency. The research methodology combines quantitative methods for data processing and qualitative methods for describing results, with data collection conducted through open-ended questionnaires focusing on the short story's structural elements (characters, setting, theme, mandate) and reader responses. The objective of literary analysis is to obtain the full meaning of a literary work by analyzing and demonstrating the relationships between the elements of the material as well as investigating the morals of the short story under study through an analysis of its psychological, sociological, and structural elements. The findings indicate that the majority of respondents (79%) identified "Search for Identity" as the core plot, (79%) perceived the main theme as "Search for Identity and Alienation", the character Tahir is predominantly portrayed as introverted and reflective (71%), the contrast between bustling and alienated Damascus and Nicosia as a symbol of hope and recovery (86%). From the perspective of reader response and experience, 79% of respondents felt emotionally connected, 57% of respondents acknowledged that their personal experiences, and (79%) agreed that interpretations of literary works can vary due to differences in individual backgrounds and experiences. This is reinforced by Tahir's experience of alienation in Damascus and his efforts to find meaning and identity in the new environment of Nicosia. This research provides insight into how readers respond to the themes raised by Youssef in a broader social and cultural context, emphasizing the crucial role of the reader as an agent in shaping meaning in literary works.